Strengthening Link and Match 8+i Program in Vocational Education: Penguatan Program Link and Match 8+i dalam Pendidikan Vokasi - Khomsah, Nur Lina; Syahri, Moh.; Tinus , Agus (Academia Open, 2025)
General background: The alignment of vocational education with industry needs is vital for producing competent graduates. Specific background: In Indonesia, the Link and Match program serves as a national strategy to bridge the gap between Vocational High Schools (SMKs) and business and industry (DUDI). Knowledge gap: However, limited empirical evidence exists on how this program is operationalized in the context of creative industries, particularly film production. Aim: This study explores the implementation of the Link and Match program at SMK Muhammadiyah 5 Kepanjen, focusing on the film expertise concentration. Results: Through qualitative analysis involving interviews, observations, and document reviews, the study finds that collaboration with three industry partners—PT Mixpro Sinema Utama, Equator Cinema, and Paradise Picture—has been realized via curriculum alignment, project-based learning, guest teaching, internships, certification, and technology adaptation. Novelty: The study highlights the comprehensive adoption of the 8+I concept, emphasizing the integration of real industry practices into school-based learning, yet reveals a lack of scholarship support post-graduation. Implications: These findings inform policymakers and educators about effective practices and critical gaps in vocational-industry synergy, especially in creative sectors. Highlights: Strengthens vocational relevance through real industry collaboration. Implements the 8+I concept across film-focused education. Reveals scholarship support as a missing program element. Keywords: Link and Match, Vocational Education, Industry Partnership, Film Production